Comparison Between Democratic and Authoritarian Parenting Styles of Sibling Rivalry in Children Aged 3-5 Years - Yomaki, Dehilda (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2025)
Parenting is a procedure applied by parents in caring for, protecting and educating their children. The purpose of this study was to determine the comparison between democratic and authoritarian parenting patterns on sibling rivalry in children aged 3-5 years at Wirawit Huntab Wondiboi Early Childhood Education. The research design used was comparative, a study that compares one variable with another that has the same object, with a cross-sectional approach. The population and sample in this study were all children aged 3-5 years at Wirawit Early Childhood Education with a sample size of 30 children divided into 2 groups, namely 15 children with democratic parenting patterns and 15 children with authoritarian parenting patterns. The results of the study using univariate and bivariate analysis and the Fisher's Exact test were conducted on the influence of democratic parenting and authoritarian parenting on sibling rivalry in children aged 3-5 years obtained a p-value = 1.0 (p-value> 0.05). The conclusion of this study is that there is no influence between democratic parenting and authoritarian parenting on the occurrence of sibling rivalry in children aged 3-5 years